A high-strength fireproof mortar and its preparation process
By adding specific components and process to the mortar, the problem of traditional cement mortar being prone to hollowing and falling off when encountering fire is solved, and high-strength fire-proof mortar with high strength and excellent fire-proof insulation performance is achieved.
Patent Information
- Application Number
- CN202411081499.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-08-08
AI Technical Summary
The traditional cement mortar used in existing buildings is prone to hollowing out when it encounters fire, and cannot meet the requirements of fireproof and heat insulation in special places such as gas stations and docks.
High-strength fire-resistant mortar is used, and its raw material components include silicate cement, sulfur-aluminate refractory cement, silicon powder, redispersible latex powder, additives, vermiculite sand, volcanic rock and flame retardant. Through specific ratios and processes, the strength and fire-proof and thermal insulation properties of the mortar are improved.
It achieves high strength, excellent adhesion, fire and heat insulation and corrosion resistance, meeting the needs of fire and heat insulation in special places.
Smart Images

Figure BDA0004983867900000071 
Figure BDA0004983867900000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of mortar, in particular to a high-strength fireproof mortar and a preparation process thereof. Background Art
[0002] A variety of building materials contribute to social development, and with them come safety issues. Especially in today's electric society, fire is a key safety concern.
[0003] Most existing buildings use steel structures with fast heat conduction, which have problems such as mechanical properties and load-bearing capacity that decrease sharply with increasing temperature. If the unprotected steel structure encounters an open flame, it will be distorted under high temperature conditions, and even cause the building to collapse and be destroyed. Therefore, fire protection measures are necessary for steel structure buildings, such as using heat-insulating and fire-proof mortar materials to improve the fire resistance of the building. However, traditional cement mortar has high density and low strength, and is prone to hollowing and falling off when encountering fire. It cannot meet the fireproof and heat-insulating requirements of special places such as gas stations and docks. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength fireproof mortar and a preparation process thereof to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A high-strength fireproof mortar comprises the following raw material components by weight: 100-150 parts of silicate cement, 115-150 parts of sulphoaluminate refractory cement, 15-30 parts of silica powder, 8-20 parts of redispersible latex powder, 2.5-4.8 parts of additives, 100-150 parts of vermiculite sand, 460-580 parts of volcanic rock and 40-80 parts of flame retardant.
[0007] Furthermore, the particle size of the volcanic rock is 30-100 mesh and the bulk density is 500-550 kg / m 3 .
[0008] Furthermore, the flame retardant is aluminum hydroxide.
[0009] Furthermore, the additive is a thickener, an air entraining agent, a retarder, and a water reducer mixed in a mass ratio of (1.8-3): (0.1-0.4): (0.1-0.4): (0.5-1).
[0010] Furthermore, the thickener is hydroxypropyl cellulose ether; the air entraining agent is sodium α-olefin sulfonate; and the retarder is sodium gluconate.
[0011] Furthermore, the water reducer is a polycarboxylate water reducer.
[0012] Furthermore, the water reducer is a silicone-modified polycarboxylic acid water reducer, and the preparation thereof comprises the following steps:
[0013] Mix allyl polyoxyethylene ether and vinyl branched polysiloxane, add a mixed solution of deionized water, acrylic acid and potassium persulfate, heat to 78-82°C and keep warm for 4-5 hours, cool down, dialyze with deionized water for 2 days, and dry to obtain an organosilicon-modified polycarboxylic acid water reducer.
[0014] Furthermore, the flame retardant is composite aluminum hydroxide, and the preparation comprises the following steps:
[0015] (1) mixing aluminum hydroxide and ethanol, adding (3-mercaptopropyl)trimethoxysilane, keeping the mixture at 48-52° C. for 10-12 hours, filtering, washing, drying, and grinding to obtain thiolated aluminum hydroxide;
[0016] (2) Adenosine monophosphate and dimethyl sulfoxide are mixed, hydrochloric acid is added, glycidyl methacrylate is added, the temperature is raised to 90-95° C. and kept warm for 6-7 hours, ethyl acetate is added, the mixture is filtered, washed, and dried to obtain a flame retardant monomer containing a double bond;
[0017] (3) Vinyl branched polysiloxane, flame retardant monomer containing double bonds and thiolated aluminum hydroxide are mixed, a mixed solution of benzoin dimethyl ether and tetrahydrofuran is added, irradiated under ultraviolet light with a wavelength of 325 nm for 20-30 min, rotary evaporated, petroleum ether is added, filtered, rotary evaporated, and dried to obtain composite aluminum hydroxide.
[0018] Furthermore, the preparation of vinyl branched polysiloxane includes the following steps: under a nitrogen atmosphere, dipropylene glycol and vinyl triethoxysilane are mixed, barium hydroxide is added, the temperature is raised to 78-82° C. until the system is clarified, the temperature is raised to 118-122° C. and kept warm for 8-12 minutes, the temperature is continued to be kept warm for 3-4 hours, the temperature is lowered, and filtering is performed to obtain vinyl branched polysiloxane.
[0019] Furthermore, a preparation process of a high-strength fireproof mortar includes the following steps: mixing silicate cement, sulphoaluminate refractory cement, silica powder and vermiculite sand, adding redispersible latex powder, additives and flame retardants, mixing and stirring, adding volcanic rock, and continuing to stir to obtain a high-strength fireproof mortar.
[0020] Beneficial effects of the present invention:
[0021] The invention provides a high-strength fireproof mortar and a preparation process thereof, which has high strength through component and ratio design, and has excellent adhesion, fireproofing, heat insulation and corrosion resistance.
[0022] Adding fireproof material vermiculite sand into the mortar makes the mortar have the advantages of high strength, low density, low thermal conductivity, etc. Volcanic rock is used as filler, and its particle size is controlled to create gaps in its porous system to play a heat insulating role. Silica powder is added as an admixture to reduce the water-to-material ratio, thereby enhancing the strength. Redispersible latex powder is selected as the adhesive material to make the prepared mortar flame retardant, low smoke and non-toxic, good elasticity and corrosion resistance.
[0023] In order to improve the fire retardancy of mortar, aluminum hydroxide is used as an environmentally friendly flame retardant. In order to solve the problems that the aluminum hydroxide surface has high hydrophilicity and polarity, poor dispersion and compatibility in the mortar, and easy aggregation, the present invention modifies the aluminum hydroxide, first uses (3-mercaptopropyl) trimethoxysilane to thiolate its surface, and then uses the photoclick of the thiol-double bond to introduce a flame retardant monomer containing a double bond and a vinyl branched polysiloxane on its surface, so that the flame retardant monomer containing a double bond and the vinyl branched polysiloxane are The branched polysiloxane has a synergistic flame retardant and fireproofing effect. The flame retardant monomer containing double bonds is prepared by modifying the small molecule flame retardant adenosine monophosphate with glycidyl methacrylate; and the vinyl branched polysiloxane is a hyperbranched polysiloxane containing a large number of Si-O bonds and double bonds synthesized from dipropylene glycol and vinyl triethoxysilane. While playing the role of flame retardant and fireproofing, it greatly improves the mortar's resistance to chloride ion penetration, reduces drying shrinkage, and improves the mortar's flexural strength.
[0024] In the present invention, allyl polyoxyethylene ether, a raw material of a high-efficiency polycarboxylic acid water-reducing agent, is used as the main chain, and vinyl branched polysiloxane with strong grafting reaction activity and acrylic acid with strong hydrophilicity are grafted to prepare an organosilicon-modified polycarboxylic acid water-reducing agent with strong hydrophilicity, high reaction activity and high water-reducing effect, thereby improving the bonding strength and corrosion resistance of the mortar, thereby extending the service life of the mortar. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0027] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0028] Embodiment 1: A process for preparing a high-strength fireproof mortar, comprising the following steps: mixing silicate cement, sulphoaluminate refractory cement, silica powder, and vermiculite sand, adding redispersible latex powder, an additive, and a flame retardant, mixing and stirring, adding volcanic rock, and continuing to stir to obtain a high-strength fireproof mortar;
[0029] The raw material components of the mortar are as follows: 130 parts of silicate cement, 120 parts of sulphoaluminate refractory cement, 25 parts of silica fume, 15 parts of redispersible latex powder, 3.9 parts of additives, 132 parts of vermiculite sand, 520 parts of volcanic rock, and 62 parts of flame retardant, in parts by mass.
[0030] The volcanic rock has a particle size of 80 mesh and a bulk density of 520 kg / m 3 ; The flame retardant is aluminum hydroxide; the auxiliary agent is a thickener, an air entraining agent, a retarder, and a water reducer compounded in a mass ratio of 2.5:0.3:0.3:0.8; the thickener is hydroxypropyl cellulose ether; the air entraining agent is sodium α-olefin sulfonate; the retarder is sodium gluconate; and the water reducer is a polycarboxylic acid water reducer.
[0031] Embodiment 2: A process for preparing a high-strength fireproof mortar, comprising the following steps: mixing silicate cement, sulphoaluminate refractory cement, silica powder, and vermiculite sand, adding redispersible latex powder, an additive, and a flame retardant, mixing and stirring, adding volcanic rock, and continuing to stir to obtain a high-strength fireproof mortar;
[0032] The raw material components of the mortar are as follows: 100 parts of silicate cement, 115 parts of sulphoaluminate refractory cement, 15 parts of silica fume, 8 parts of redispersible latex powder, 2.5 parts of additives, 100 parts of vermiculite sand, 460 parts of volcanic rock, and 40 parts of flame retardant, in parts by mass.
[0033] The volcanic rock has a particle size of 30 mesh and a bulk density of 500 kg / m 3 ;
[0034] The auxiliary agent is a thickener, an air entraining agent, a retarder, and a water reducer in a mass ratio of 1.8:0.1:0.1:0.5; the thickener is hydroxypropyl cellulose ether; the air entraining agent is sodium α-olefin sulfonate; the retarder is sodium gluconate;
[0035] The water reducer is an organosilicon-modified polycarboxylic acid water reducer, and the preparation thereof comprises the following steps:
[0036] 42 g of allyl polyoxyethylene ether and 12 g of vinyl branched polysiloxane were mixed, and a mixed solution of 100 mL of deionized water, 56 g of acrylic acid, and 1 g of potassium persulfate was added, and the mixture was heated to 78°C and kept for 5 h, cooled, dialyzed with deionized water for 2 d, and dried to obtain an organosilicon-modified polycarboxylic acid water reducer;
[0037] The flame retardant is composite aluminum hydroxide, and the preparation thereof comprises the following steps:
[0038] (1) 30 g of aluminum hydroxide and 300 g of ethanol were mixed, 8 g of (3-mercaptopropyl)trimethoxysilane was added, the mixture was kept at 48° C. for 12 h, filtered, washed, dried, and ground to obtain thiolated aluminum hydroxide;
[0039] (2) 6 g of adenosine monophosphate and 40 mL of dimethyl sulfoxide were mixed, 2.2 mL of 0.1 mol / L hydrochloric acid solution was added, 5 mL of glycidyl methacrylate was added, the temperature was raised to 90° C. and kept warm for 7 h, 100 mL of ethyl acetate was added, the mixture was filtered, washed, and dried to obtain a flame retardant monomer containing a double bond;
[0040] (3) 6.2 g of vinyl branched polysiloxane, 4.5 g of a flame retardant monomer containing a double bond, and 12.6 g of thiolated aluminum hydroxide were mixed, 0.2 g of benzoin dimethyl ether and 80 mL of tetrahydrofuran were added, and the mixture was irradiated under an ultraviolet lamp with a wavelength of 325 nm for 20 min, and rotary evaporated, 50 mL of petroleum ether was added, filtered, rotary evaporated, and dried to obtain composite aluminum hydroxide;
[0041] The preparation of the vinyl branched polysiloxane comprises the following steps: under a nitrogen atmosphere, 2.41 g of dipropylene glycol and 1.9 g of vinyl triethoxysilane are mixed, 0.02 g of barium hydroxide is added, the temperature is raised to 78° C. until the system is clear, the temperature is raised to 118° C. and kept warm for 12 min, the temperature is continued to be kept warm for 3 h, the temperature is lowered, and filtering is performed to obtain the vinyl branched polysiloxane.
[0042] Embodiment 3: A process for preparing a high-strength fireproof mortar, comprising the following steps: mixing silicate cement, sulphoaluminate refractory cement, silica powder, and vermiculite sand, adding redispersible latex powder, an additive, and a flame retardant, mixing and stirring, adding volcanic rock, and continuing to stir to obtain a high-strength fireproof mortar;
[0043] The raw material components of the mortar are as follows: 130 parts of silicate cement, 120 parts of sulphoaluminate refractory cement, 25 parts of silica fume, 15 parts of redispersible latex powder, 3.9 parts of additives, 132 parts of vermiculite sand, 520 parts of volcanic rock, and 62 parts of flame retardant, in parts by mass.
[0044] The volcanic rock has a particle size of 80 mesh and a bulk density of 520 kg / m 3 ;
[0045] The auxiliary agent is a thickener, an air entraining agent, a retarder, and a water reducer in a mass ratio of 2.5:0.3:0.3:0.8; the thickener is hydroxypropyl cellulose ether; the air entraining agent is sodium α-olefin sulfonate; the retarder is sodium gluconate;
[0046] The water reducer is an organosilicon-modified polycarboxylic acid water reducer, and the preparation thereof comprises the following steps:
[0047] 42 g of allyl polyoxyethylene ether and 12 g of vinyl branched polysiloxane were mixed, and a mixed solution of 100 mL of deionized water, 56 g of acrylic acid, and 1 g of potassium persulfate was added, and the mixture was heated to 80° C. and kept for 4.5 h, cooled, dialyzed with deionized water for 2 d, and dried to obtain an organosilicon-modified polycarboxylic acid water reducer;
[0048] The flame retardant is composite aluminum hydroxide, and the preparation thereof comprises the following steps:
[0049] (1) 30 g of aluminum hydroxide and 300 g of ethanol were mixed, 8 g of (3-mercaptopropyl)trimethoxysilane was added, the mixture was kept at 50° C. for 11 h, filtered, washed, dried, and ground to obtain thiolated aluminum hydroxide;
[0050] (2) 6 g of adenosine monophosphate and 40 mL of dimethyl sulfoxide were mixed, 2.2 mL of 0.1 mol / L hydrochloric acid solution was added, 5 mL of glycidyl methacrylate was added, the temperature was raised to 92° C. and kept warm for 6.5 h, 100 mL of ethyl acetate was added, the mixture was filtered, washed, and dried to obtain a flame retardant monomer containing a double bond;
[0051] (3) 6.2 g of vinyl branched polysiloxane, 4.5 g of a flame retardant monomer containing a double bond, and 12.6 g of thiolated aluminum hydroxide were mixed, 0.2 g of benzoin dimethyl ether and 80 mL of tetrahydrofuran were added, and the mixture was irradiated under an ultraviolet lamp with a wavelength of 325 nm for 25 min, and then rotary evaporated, 50 mL of petroleum ether was added, filtered, rotary evaporated, and dried to obtain composite aluminum hydroxide;
[0052] The preparation of the vinyl branched polysiloxane comprises the following steps: under a nitrogen atmosphere, 2.41 g of dipropylene glycol and 1.9 g of vinyl triethoxysilane are mixed, 0.02 g of barium hydroxide is added, the temperature is raised to 80° C. until the system is clarified, the temperature is raised to 120° C. and kept warm for 10 min, the temperature is kept warm for 3.5 h, the temperature is lowered, and the vinyl branched polysiloxane is filtered to obtain the vinyl branched polysiloxane.
[0053] Embodiment 4: A process for preparing a high-strength fireproof mortar, comprising the following steps: mixing silicate cement, sulphoaluminate refractory cement, silica powder, and vermiculite sand, adding redispersible latex powder, an additive, and a flame retardant, mixing and stirring, adding volcanic rock, and continuing to stir to obtain a high-strength fireproof mortar;
[0054] The raw material components of the mortar are as follows: 150 parts of silicate cement, 150 parts of sulphoaluminate refractory cement, 30 parts of silica fume, 20 parts of redispersible latex powder, 4.8 parts of additives, 150 parts of vermiculite sand, 580 parts of volcanic rock, and 80 parts of flame retardant by weight.
[0055] The volcanic rock has a particle size of 100 mesh and a bulk density of 550 kg / m 3 ;
[0056] The auxiliary agent is a thickener, an air entraining agent, a retarder, and a water reducer in a mass ratio of 3:0.4:0.4:1; the thickener is hydroxypropyl cellulose ether; the air entraining agent is sodium α-olefin sulfonate; the retarder is sodium gluconate;
[0057] The water reducer is an organosilicon-modified polycarboxylic acid water reducer, and the preparation thereof comprises the following steps:
[0058] 42 g of allyl polyoxyethylene ether and 12 g of vinyl branched polysiloxane were mixed, and a mixed solution of 100 mL of deionized water, 56 g of acrylic acid, and 1 g of potassium persulfate was added, and the mixture was heated to 82° C. and kept for 4 h, cooled, dialyzed with deionized water for 2 d, and dried to obtain an organosilicon-modified polycarboxylic acid water reducer;
[0059] The flame retardant is composite aluminum hydroxide, and the preparation thereof comprises the following steps:
[0060] (1) 30 g of aluminum hydroxide and 300 g of ethanol were mixed, 8 g of (3-mercaptopropyl)trimethoxysilane was added, the mixture was kept at 52° C. for 10 h, filtered, washed, dried, and ground to obtain thiolated aluminum hydroxide;
[0061] (2) 6 g of adenosine monophosphate and 40 mL of dimethyl sulfoxide were mixed, 2.2 mL of 0.1 mol / L hydrochloric acid solution was added, 5 mL of glycidyl methacrylate was added, the temperature was raised to 95° C. and kept for 6 h, 100 mL of ethyl acetate was added, the mixture was filtered, washed, and dried to obtain a flame retardant monomer containing a double bond;
[0062] (3) 6.2 g of vinyl branched polysiloxane, 4.5 g of a flame retardant monomer containing a double bond, and 12.6 g of thiolated aluminum hydroxide were mixed, 0.2 g of benzoin dimethyl ether and 80 mL of tetrahydrofuran were added, and the mixture was irradiated under an ultraviolet lamp with a wavelength of 325 nm for 30 min, and then rotary evaporated, 50 mL of petroleum ether was added, filtered, rotary evaporated, and dried to obtain composite aluminum hydroxide;
[0063] The preparation of the vinyl branched polysiloxane comprises the following steps: under a nitrogen atmosphere, 2.41 g of dipropylene glycol and 1.9 g of vinyl triethoxysilane are mixed, 0.02 g of barium hydroxide is added, the temperature is raised to 82° C. until the system is clarified, the temperature is raised to 122° C. and kept warm for 8 minutes, the temperature is continued to be kept warm for 4 hours, the temperature is lowered, and filtering is performed to obtain the vinyl branched polysiloxane.
[0064] Comparative Example 1: Example 1 was used as a control group, no vermiculite sand was added, and other processes were normal.
[0065] Comparative Example 2: Taking Example 3 as the control group, the composite aluminum hydroxide was replaced with thiolated aluminum hydroxide, and the other processes were normal.
[0066] Comparative Example 3: Taking Example 3 as the control group, the organosilicon-modified polycarboxylate water-reducing agent was replaced by a polycarboxylate water-reducing agent, and the other processes were normal.
[0067] Comparative Example 4: Example 3 was used as a control group, vinyl branched polysiloxane was not prepared, and other processes were normal.
[0068] Source of raw materials (for demonstration only):
[0069] Portland cement P.O525: Hainan Huasheng Tianya Co., Ltd.; sulphoaluminate refractory cement S.SAC525: Gongyi Sanhe Refractory Material Co., Ltd.; silica fume (grade 96): Hebei Yirui Alloy Welding Material Co., Ltd.; vermiculite sand (10-20 mesh): Lingshou County Anda Mineral Powder Factory; redispersible latex powder 5044N: Guangdong Longhu Technology Materials Co., Ltd.; hydroxypropyl cellulose ether H100: Shandong Yiteng Cellulose Co., Ltd.; sodium α-olefin sulfonate AOS: Zhejiang Zanyu Technology Group Co., Ltd.; sodium gluconate: Jinan Qihang Chemical Technology Co., Ltd.; polycarboxylate water reducer P622: Suzhou Xingbang Chemical Building Materials Co., Ltd.; aluminum hydroxide SS-AL0 4: Wuhu Jikang New Materials Technology Co., Ltd.; adenosine monophosphate (98%): Chengdu Huaxia Chemical Co., Ltd.; benzoin dimethyl ether S45044: Shanghai Yuanye Biotechnology Co., Ltd.; allyl polyoxyethylene ether A303301, acrylic acid A103526, (3-mercaptopropyl) trimethoxysilane M100619, dimethyl sulfoxide D103272, glycidyl methacrylate G106686, tetrahydrofuran T103263, dipropylene glycol D105105, vinyl triethoxysilane T103647: Aladdin reagent; potassium persulfate, ethanol, hydrochloric acid, ethyl acetate, petroleum ether, barium hydroxide, analytical grade: Sinopharm Group reagent.
[0070] Performance test: The mortars prepared in the embodiments and comparative examples were subjected to performance tests:
[0071] When the performance test was performed, the mass ratio of mortar to purified water in the embodiment and the comparative example was 1:5.8;
[0072] Bond strength and compressive strength: refer to JGJ70-2009 test method for basic properties of building mortar for testing; thermal conductivity: refer to GB / T10297 thermal conductivity of non-metallic solid materials for testing; fire resistance: refer to GB14907-2018 fire resistance performance test method for steel structure fire retardant coating for testing; the results are shown in Table 1;
[0073] Table 1
[0074]
[0075]
[0076] The invention provides a high-strength fireproof mortar and a preparation process thereof, which has high strength through component and ratio design, and has excellent adhesion, fireproofing, heat insulation and corrosion resistance.
[0077] Comparing Example 1 with Comparative Example 1, vermiculite sand, a fireproof material, is added to the mortar, so that the mortar has the advantages of high strength, low density, low thermal conductivity, etc.
[0078] Example 3 is compared with Comparative Example 2 and Comparative Example 4. In order to improve the fire retardancy of the mortar, aluminum hydroxide is used as an environmentally friendly flame retardant. In order to solve the problems that the aluminum hydroxide surface has high hydrophilicity and polarity, poor dispersion and compatibility in the mortar, and easy aggregation, the present invention modifies the aluminum hydroxide, firstly uses (3-mercaptopropyl) trimethoxysilane to thiolate its surface, and then uses the photoclick of the thiol-double bond to introduce a flame retardant monomer containing a double bond and a vinyl branched polysiloxane on its surface, so that it can be formed on the surface of the aluminum hydroxide containing a double bond. The flame retardant monomer and vinyl branched polysiloxane play a synergistic flame retardant and fireproofing effect. The flame retardant monomer containing double bonds is a flame retardant monomer prepared by modifying the expandable small molecule flame retardant adenosine monophosphate with glycidyl methacrylate; and the vinyl branched polysiloxane is a hyperbranched polysiloxane containing a large number of Si-O bonds and double bonds synthesized from dipropylene glycol and vinyl triethoxysilane. While playing the role of flame retardant and fireproofing, it greatly improves the mortar's resistance to chloride ion penetration, reduces drying shrinkage, and improves the mortar's flexural strength.
[0079] By comparing Example 3 with Comparative Examples 3 and 4, in the present invention, the raw material of high-efficiency polycarboxylic acid water-reducing agent, allyl polyoxyethylene ether, is used as the main chain, and vinyl branched polysiloxane with strong grafting reaction activity and acrylic acid with strong hydrophilicity are used to prepare an organosilicon-modified polycarboxylic acid water-reducing agent with strong hydrophilicity, high reaction activity and high water-reducing effect, thereby improving the bonding strength and corrosion resistance of the mortar, thereby extending the service life of the mortar.
[0080] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A high-strength fireproof mortar, characterized in that: The raw material components of the mortar are as follows: 100-150 parts of silicate cement, 115-150 parts of sulphoaluminate refractory cement, 15-30 parts of silica fume, 8-20 parts of redispersible latex powder, 2.5-4.8 parts of additives, 100-150 parts of vermiculite sand, 460-580 parts of volcanic rock, and 40-80 parts of flame retardant, in parts by mass. The flame retardant is composite aluminum hydroxide, and the preparation thereof comprises the following steps: (1) mixing aluminum hydroxide and ethanol, adding (3-mercaptopropyl)trimethoxysilane, keeping the mixture at 48-52° C. for 10-12 hours, filtering, washing, drying, and grinding to obtain thiolated aluminum hydroxide; (2) Adenosine monophosphate and dimethyl sulfoxide are mixed, hydrochloric acid is added, glycidyl methacrylate is added, the temperature is raised to 90-95° C. and kept warm for 6-7 hours, ethyl acetate is added, the mixture is filtered, washed, and dried to obtain a flame retardant monomer containing a double bond; (3) Vinyl branched polysiloxane, flame retardant monomer containing double bonds and thiolated aluminum hydroxide are mixed, a mixed solution of benzoin dimethyl ether and tetrahydrofuran is added, irradiated under ultraviolet light with a wavelength of 325 nm for 20-30 min, rotary evaporated, petroleum ether is added, filtered, rotary evaporated, and dried to obtain composite aluminum hydroxide.
2. A high-strength fireproof mortar according to claim 1, characterized in that: The volcanic rock has a particle size of 30-100 mesh and a bulk density of 500-550 kg / m 3 .
3. A high-strength fireproof mortar according to claim 1, characterized in that: The auxiliary agent is a thickener, an air entraining agent, a retarder and a water reducer which are compounded in a mass ratio of (1.8-3): (0.1-0.4): (0.1-0.4): (0.5-1).
4. A high-strength fireproof mortar according to claim 3, characterized in that: The thickener is hydroxypropyl cellulose ether; the air entraining agent is sodium α-olefin sulfonate; and the retarder is sodium gluconate.
5. The high-strength fireproof mortar according to claim 3, characterized in that: The water reducer is a polycarboxylate water reducer.
6. The high-strength fireproof mortar according to claim 3, characterized in that: The water reducer is an organosilicon-modified polycarboxylic acid water reducer, and the preparation thereof comprises the following steps: Mix allyl polyoxyethylene ether and vinyl branched polysiloxane, add a mixed solution of deionized water, acrylic acid and potassium persulfate, heat to 78-82°C and keep warm for 4-5 hours, cool down, dialyze with deionized water for 2 days, and dry to obtain an organosilicon-modified polycarboxylic acid water reducer.
7. The high-strength fireproof mortar according to claim 1, characterized in that: The preparation of the vinyl branched polysiloxane comprises the following steps: in a nitrogen atmosphere, dipropylene glycol and vinyl triethoxysilane are mixed, barium hydroxide is added, the temperature is raised to 78-82° C. until the system is clear, the temperature is raised to 118-122° C. and kept warm for 8-12 minutes, the temperature is kept warm for 3-4 hours, the temperature is lowered, and filtering is performed to obtain the vinyl branched polysiloxane.
8. A process for preparing a high-strength fireproof mortar according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mix silicate cement, sulphoaluminate refractory cement, silica powder and vermiculite sand, add redispersible latex powder, additives and flame retardant, mix and stir, add volcanic rock and continue stirring to obtain a high-strength fireproof mortar.
Citation Information
Patent Citations
Insulating dry powder mortar
CN101525226A
Hyperbranched polysiloxane as well as preparation method and application thereof
CN110229338A
Heat preservation and fire resistance integrated spray type mortar
CN110317021A
Prestressed duct grouting material
CN111943604A